Psoriasis in teledermatology: analysis of the 2016‒2020 period in Santa Catarina - Maria Laura Orlandi Demo; Daniel Holthausen Nunes; Chaiana Esmeraldino Mendes Marcon (Sociedade Brasileira de Dermatologia, 2023)
Abstract Background Psoriasis is a skin disease that affects 1.3% of Brazilians. The use of teledermatology (TD) in the public health sector has democratized access to dermatological care. Objective To analyze TD exams with suspected and/or diagnosed psoriasis performed between 2016‒2020 in the state of Santa Catarina (SC). Methods Analytical cross-sectional observational study that used secondary data collected from the records of TD exams from the Telemedicine and Telehealth System (TTS) of SC. The associations were evaluated by the chi-square test and Student'st test. The significance level was set at 5% (p < 0.05). Results During the period, 6,146 TD exams were related to psoriasis, 58% due to the diagnosis provided by the reporting dermatologist and 42% exclusively due to the suspected disease on the request of the examination. The male sex predominated among the diagnoses of dermatosis (51%; p < 0.001). Regarding risk classification, psoriasis diagnoses were predominantly yellow (58.7%; p < 0.001) or blue (39.7%; p < 0.001) risk, respectively indicating moderate to severe psoriasis (referral to tertiary care) and mild psoriasis (treatment in the primary health care [PHC] level). True positive tests, suspected by PHC and diagnosed with psoriasis through TD, were 34.1% (p < 0.001). Study limitations The TD service is available only for the public health network and analysis for a limited period (five years). Conclusions Psoriasis diagnoses performed by TD, when compared to other dermatoses, tend to receive treatment at the primary (p < 0.001) or tertiary (p < 0.001) health care level, reducing the number of referrals to the secondary care level.